Resin particles, conductive particles, conductive materials and connection structures

By compressing resin particles to form planar portions and integrating conductive portions, the solution addresses issues of contact area and frictional resistance, enhancing electrical connections and gap control in electronic devices.

JP7617001B2Active Publication Date: 2025-01-17SEKISUI CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021537377
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-12
Filing Date
2020-08-06
Publication Date
2025-01-17
Estimated Expiration
2040-08-06

AI Technical Summary

Technical Problem

Conventional conductive particles and resin spacers exhibit insufficient contact area and frictional resistance, leading to high connection resistance, interfacial peeling, and unreliable gap control in electronic connections.

Method used

Resin particles are compressed by 30% relative to their diameter and held at 200°C for 10 minutes to form planar portions, enhancing contact area and frictional resistance, and are used in conjunction with conductive portions to form conductive particles for improved electrical connections and spacers for uniform gap control.

Benefits of technology

The modified resin particles increase contact area and suppress interfacial peeling, reducing connection resistance and ensuring reliable electrical conductivity and uniform thickness in electronic connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617001000003
    Figure 0007617001000003
  • Figure 0007617001000004
    Figure 0007617001000004
  • Figure 0007617001000005
    Figure 0007617001000005
Patent Text Reader

Abstract

Provided is a resin particle which makes it possible to bring about increases in the area of contact between the resin particle or a particle comprising the resin particle and an adherend and in the resistance of friction therebetween and hence to inhibit interfacial separation between the resin particle or particle comprising the resin particle and the adherend. When this resin particle is held at 200°C for 10 minutes in the state of being compressed by 30% with respect to the particle diameter and thereafter released from the compression, then the released resin particle has two flat portions which face each other in the compression direction.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin particle having good compression characteristics. The present invention also relates to a conductive particle, a conductive material, and a connection structure using the resin particle. [Background technology]

[0002] Anisotropic conductive materials, such as anisotropic conductive pastes and anisotropic conductive films, are widely known, in which conductive particles are dispersed in a binder.

[0003] The anisotropic conductive material is used to electrically connect between electrodes of various connection target members such as flexible printed circuit boards (FPCs), glass substrates, glass epoxy substrates, and semiconductor chips, to obtain a connection structure. In addition, as the conductive particles, conductive particles having resin particles and conductive parts arranged on the surfaces of the resin particles may be used.

[0004] A liquid crystal display element is configured by disposing a liquid crystal between two glass substrates. In the liquid crystal display element, a spacer is used as a gap control material to keep the distance (gap) between the two glass substrates uniform and constant. Resin particles are generally used as the spacer.

[0005] The following Patent Document 1 discloses a photosensitive composition for color filters, which contains at least a resin (A) containing an acidic group and a group having an ethylenically unsaturated bond in a side chain, a polymerizable compound (B) containing two or more polymerizable substituents having an ethylenically unsaturated bond and a divalent or higher ring structure-containing group bonded to the polymerizable substituent, and a photopolymerization initiator (C). Patent Document 1 describes that the photosensitive composition preferably contains fine particles (D) and that a photospacer can be formed using the photosensitive composition. In the examples of Patent Document 1, the deformation recovery rate of the photospacer formed by the photosensitive composition is evaluated, but it is merely described that the deformation recovery rate is preferably high. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-162871 A Summary of the Invention [Problem to be solved by the invention]

[0007] With conventional conductive particles, when conductively connecting electrodes, the conductive particles may not be deformed sufficiently, or the compressed conductive particles may try to return to their original shape. In this case, the contact area between the conductive particles and the electrode (adherend) may not be large enough, or peeling may occur at the interface between the conductive particles and the electrode, resulting in an increase in connection resistance and a decrease in electrical reliability.

[0008] Furthermore, when conventional resin particles are used as spacers, the contact area and frictional resistance between the resin particles and the members to be connected (adherend) are not sufficiently large, and the resin particles may not be fixed in a predetermined position due to rolling, etc. In this case, peeling occurs at the interface between the resin particles and the members to be connected, making it impossible to control the thickness between the members to be connected uniformly, and the function as a spacer may not be fully exerted.

[0009] The object of the present invention is to provide a resin particle that can increase the contact area and frictional resistance between the resin particle or the particle using the resin particle and the adherend, and therefore can suppress interfacial peeling between the resin particle or the particle using the resin particle and the adherend. Another object of the present invention is to provide a conductive particle, a conductive material, and a connection structure using the above resin particle. [Means for solving the problem]

[0010] According to a broad aspect of the present invention, there is provided a resin particle, which is compressed by 30% relative to its particle diameter, held at 200°C for 10 minutes, and then released from compression, such that the resin particle after release from compression has two planar portions facing each other in the compression direction.

[0011] In a specific aspect of the resin particles according to the present invention, the ratio of the major axis of the flat portion of the resin particle after the compression and release to the maximum axis of the resin particle after the compression and release is 0.10 or more and 0.95 or less.

[0012] In a specific aspect of the resin particles according to the present invention, the thermal decomposition temperature is 200° C. or more and 350° C. or less.

[0013] In a specific aspect of the resin particles according to the present invention, the compressive elastic modulus when compressed by 10% is 100 N / mm 2 More than 3500N / mm 2 The following is the result.

[0014] In a specific aspect of the resin particles according to the present invention, the compressive elastic modulus when compressed by 30% is 100 N / mm 2 More than 3000N / mm 2 The following is the result.

[0015] In certain aspects of the resin particles according to the present invention, the resin particles are used as spacers, as adhesives for electronic components, for obtaining conductive particles having conductive portions, or as materials for additive manufacturing.

[0016] In a specific aspect of the resin particles according to the present invention, the resin particles are used as spacers for liquid crystal display elements, as adhesives for electronic components, or for obtaining conductive particles having conductive portions.

[0017] According to a broad aspect of the present invention, there is provided a conductive particle comprising the above-described resin particle and a conductive portion disposed on a surface of the resin particle.

[0018] In a specific aspect of the conductive particle according to the present invention, the conductive particle further includes an insulating material disposed on an outer surface of the conductive portion.

[0019] In a specific aspect of the conductive particle according to the present invention, the conductive particle has protrusions on an outer surface of the conductive portion.

[0020] According to a broad aspect of the present invention, there is provided a conductive material comprising conductive particles and a binder resin, the conductive particles comprising the above-mentioned resin particles and a conductive portion disposed on a surface of the resin particles.

[0021] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member, a second connection target member, and a connection portion connecting the first connection target member and the second connection target member, the connection portion being formed from the above-mentioned resin particles or from a composition containing the resin particles.

[0022] According to a broad aspect of the present invention, there is provided a connection structure comprising: a first connection target member having a first electrode on its surface; a second connection target member having a second electrode on its surface; and a connection portion connecting the first connection target member and the second connection target member, wherein the connection portion is formed from conductive particles or from a conductive material containing the conductive particles and a binder resin, the conductive particles comprise the above-mentioned resin particles and a conductive portion arranged on the surface of the resin particles, and the first electrode and the second electrode are electrically connected by the conductive particles. Effect of the Invention

[0023] The resin particles according to the present invention have two flat surfaces that face each other in the compression direction when the resin particles are compressed by 30% relative to the particle diameter, held at 200°C for 10 minutes, and then released from compression. Since the resin particles according to the present invention have the above-mentioned configuration, the contact area and frictional resistance between the resin particles or particles using resin particles and an adherend can be increased, and therefore interfacial peeling between the resin particles or particles using resin particles and an adherend can be suppressed. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a cross-sectional view showing a resin particle according to a first embodiment of the present invention, where FIG. 1(a) is a cross-sectional view showing the resin particle before compression, and FIG. 1(b) is a cross-sectional view showing the resin particle after release from compression. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing an example of a connection structure using conductive particles according to the first embodiment of the present invention. [Figure 6] FIG. 6 is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention. [Figure 7] FIG. 7 is an enlarged cross-sectional view showing a joint portion of the electronic component device shown in FIG. [Figure 8] FIG. 8(a) is a typical electron microscope photograph of resin particles (resin particles before thermal curing), and FIG. 8(b) is a typical electron microscope photograph of resin particles after compression and release. [Figure 9] FIG. 9 is an electron microscope photograph of the resin particles in Reference Example 8 after being released from compression. [Figure 10]FIG. 10(a) is an electron microscope photograph of resin particles after compression and release in Comparative Example 1, FIG. 10(b) is an electron microscope photograph of resin particles after compression and release in Comparative Example 2, and FIG. 10(c) is an electron microscope photograph of resin particles after compression and release in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below.

[0026] (Resin particles) The resin particles according to the present invention are compressed by 30% relative to their particle diameter, held at 200°C for 10 minutes, and then released from compression, so that the resin particles after release from compression have two planar portions that face each other in the compression direction.

[0027] Since the resin particles according to the present invention have the above-mentioned configuration, it is possible to increase the contact area and frictional resistance between the resin particles or particles using resin particles and the adherend, and therefore it is possible to suppress interfacial peeling between the resin particles or particles using resin particles and the adherend.

[0028] The resin particles according to the present invention can be thermoset by heating. The resin particles according to the present invention can be thermoset by heating. The resin particles according to the present invention (resin particles before thermosetting) are not completely thermoset, and can well maintain the compressed shape when heated and compressed. Whether the resin particles according to the present invention can be thermoset can be confirmed as follows.

[0029] The resin particles before heat curing are heated at 200°C for 1 hour, and then cooled at 25°C for 1 hour. The change in the compressive modulus before and after heat curing is calculated by the following formula from the compressive modulus (10% K value) when the resin particles after heating and cooling are compressed by 10% and the compressive modulus (10% K value) when the resin particles before heat curing are compressed by 10%. When the change in the modulus before and after heat curing calculated by the following formula is 105% or more, it is considered that heat curing has occurred due to heating, and the particles are considered to be heat curable by heating. The 10% K value of the resin particles can be measured by the method described below.

[0030] Rate of change in compressive elastic modulus before and after heat curing (%) = (10% K value of resin particles after heating and cooling) / (10% K value of resin particles before heat curing) x 100

[0031] When the resin particles according to the present invention are used as conductive particles having a conductive portion formed on the surface of the resin particles, the conductive particles are deformed well during thermocompression bonding between the conductive particles and an electrode (adherend), and the compressed shape is maintained even after thermocompression bonding, so that the contact area between the conductive particles and the electrode can be increased. Therefore, it is possible to suppress interfacial peeling between the conductive particles and the electrode, and further, it is possible to effectively suppress damage to the electrode. In addition, when the electrodes are electrically connected, it is possible to increase the adhesion between the resin particles and the conductive portion in the conductive particles. Therefore, in the conductive particles using the resin particles according to the present invention, it is possible to effectively reduce the connection resistance of the connection structure in which the electrodes are electrically connected by the conductive particles, and it is possible to increase the conduction reliability. In addition, even if the connection structure is left for a long time under high temperature and high humidity conditions, the connection resistance is unlikely to increase, and conduction failure is unlikely to occur. Furthermore, even if the connection structure is dropped and subjected to an impact, it is possible to suppress interfacial peeling between the conductive particles and the electrode.

[0032] Furthermore, when the resin particles according to the present invention are used as a spacer (gap material) or an adhesive for electronic components, the resin particles deform well during thermocompression bonding between the resin particles and the member to be connected (adherend), and the compressed shape is maintained even after thermocompression bonding, so that the contact area and frictional resistance between the resin particles and the member to be connected can be increased, and the resin particles can be easily fixed at a predetermined position. Therefore, a spacer or an adhesive for electronic components using the resin particles according to the present invention can suppress interfacial peeling between the resin particles and the member to be connected. A spacer or an adhesive for electronic components using the resin particles according to the present invention can uniformly control the thickness between the members to be connected.

[0033] The resin particles according to the present invention have two flat surfaces facing each other in the compression direction when the resin particles are compressed by 30% relative to their particle diameter, held at 200° C. for 10 minutes, and then released from compression. The resin particles according to the present invention have compression characteristics different from those of conventional resin particles.

[0034] As a method for making the resin particles have two plane parts facing each other in the compression direction after compression and release, for example, a method using resin particles having flexibility and low restorability can be mentioned. As a method for obtaining resin particles having flexibility and low restorability, for example, a method for lowering the reaction temperature during the production of resin particles can be mentioned. More specifically, a method for producing resin particles using a thermosetting resin as the material of the resin particles and suppressing the reaction temperature to 80°C or less (preferably 70°C or less) can be mentioned.

[0035] The compression of the resin particles and the observation of the resin particles after release from the compression are specifically carried out as follows.

[0036] A first plate and a second plate are prepared. The first plate and the second plate each have a flat surface. A polyimide film having a thickness of 70% of the particle diameter of the resin particles is attached to the end of the surface of the first plate or the second plate as a gap material. The first plate and the second plate are heated so that the surface temperature is 200°C. Resin particles are placed on the surface of the heated first plate. Using a digital vice heat press (for example, "MNP2-002D" manufactured by AS ONE Corporation), the first plate or the second plate is moved to a position where the distance between the first plate and the second plate is 70% of the particle diameter of the resin particles. That is, the resin particles are compressed by 30% with respect to the particle diameter. The resin particles are compressed at the flat portions of the first plate and the second plate. The compression conditions are a compression speed of 2000 mN / sec and a load of 20000 mN. The resin particles are compressed by 30% and held at 200°C for 10 minutes under a load of 20,000 mN, and then released from compression. The resin particles after release are left to stand for 1 hour at 25°C under windless conditions, and then photographed with an electron microscope or optical microscope to observe the shape of the resin particles.

[0037] The material of the first plate and the second plate is preferably glass, stainless steel (SUS), or silicon, and more preferably glass.

[0038] The particle size of the resin particles is preferably an average particle size, and more preferably a number average particle size. The method for measuring the particle size of the resin particles will be described later.

[0039] The resin particles do not have to be used after being heated to, for example, 200° C., and do not have to be used in a state compressed by 30%. The observation of the resin particles after compression and release of compression is performed to evaluate the compression characteristics of the resin particles.

[0040] Fig. 1 is a cross-sectional view showing a resin particle according to a first embodiment of the present invention. Fig. 1(a) is a cross-sectional view showing a resin particle before compression, and Fig. 1(b) is a cross-sectional view showing a resin particle after compression and release. Fig. 8(a) shows a typical electron microscope photograph of a resin particle (resin particle before thermal curing), and Fig. 8(b) shows a typical electron microscope photograph of a resin particle after compression and release.

[0041] The shape of the resin particle 1 before compression shown in FIG. 1(a) is spherical. The resin particle 1 after compression and release shown in FIG. 1(b) is a resin particle after compression and release when the resin particle 1 shown in FIG. 1(a) is compressed by 30% relative to the particle diameter, held at 200°C for 10 minutes, and then released from compression. The resin particle 1 after compression and release shown in FIG. 1(b) has a first surface 1a (flat surface portion) and a second surface 1b (flat surface portion) facing each other in the compression direction P. The first surface 1a and the second surface 1b are formed from the surfaces of the first plate and the second plate used when the resin particle 1 is compressed by 30%. The first surface 1a and the second surface 1b are flat surfaces. The shapes of the first surface 1a and the second surface 1b are each circular.

[0042] The major axis of the flat surface of the resin particle after compression and release is A. The longest diameter of the resin particle after compression and release is B. In the resin particle 1 after compression and release shown in FIG. 1(b), the first surface 1a and the second surface 1b are each circular in shape, so A is the diameter of the flat surface. In the resin particle 1 after compression and release shown in FIG. 1(b), B is the major axis of the resin particle 1 in a direction perpendicular to the compression direction P. The major axis A of the surface of the resin particle after compression and the longest diameter B of the resin particle after compression and release can be calculated, for example, by observing the resin particle after compression and release from a direction perpendicular to the compression direction.

[0043] From the viewpoint of exerting the effects of the present invention more effectively, the ratio of A to B (A / B) is preferably 0.10 or more, more preferably 0.15 or more, even more preferably 0.30 or more, particularly preferably 0.40 or more, most preferably 0.60 or more, and preferably 0.95 or less, more preferably 0.90 or less, even more preferably 0.85 or less, particularly preferably 0.80 or less. The ratio (A / B) is preferably determined by observing 50 arbitrary resin particles with an electron microscope or optical microscope and calculating the average ratio (A / B) of each resin particle.

[0044] The aspect ratio of the resin particles (before compression) is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less. The aspect ratio of the resin particles (before compression) indicates the major axis / minor axis. The aspect ratio of the resin particles (before compression) is preferably determined by observing 50 arbitrary resin particles with an electron microscope or optical microscope, taking the maximum diameter and the minimum diameter as the major axis and the minor axis, respectively, and calculating the average major axis / minor axis value of each resin particle.

[0045] The aspect ratio of the resin particles after compression and release observed from a direction perpendicular to the compression direction is generally greater than 1. The aspect ratio of the resin particles after compression and release observed from a direction perpendicular to the compression direction may be 1.1 or more, 1.3 or more, 5 or less, 3 or less, 2 or less, or 1.5 or less. The aspect ratio of the resin particles after compression and release indicates the major axis / minor axis of the resin particles observed from a direction perpendicular to the compression direction. The aspect ratio of the resin particles after compression and release is preferably determined by observing 50 arbitrary resin particles with an electron microscope or optical microscope, taking the maximum diameter and the minimum diameter of the resin particles observed from a direction perpendicular to the compression direction as the major axis and the minor axis, respectively, and calculating the average major axis / minor axis of each resin particle. For example, in the resin particle 1 after compression and release shown in Figure 1 (b), the above aspect ratio is the ratio of the longest diameter B of the resin particle after compression and release to the distance between the first surface 1a (flat portion) and the second surface 1b (flat portion) in the compression direction (longest diameter B of the resin particle after compression and release / distance between the first surface 1a (flat portion) and the second surface 1b (flat portion) in the compression direction).

[0046] As a method for satisfying the aspect ratio of the resin particles after compression and release observed from a direction perpendicular to the compression direction within the above range, for example, a method using resin particles having flexibility and low restorability can be mentioned. As a method for obtaining resin particles having flexibility and low restorability, for example, a method for lowering the reaction temperature during the preparation of the resin particles can be mentioned. More specifically, a method for preparing the resin particles using a thermosetting resin as the material for the resin particles and suppressing the reaction temperature to 80° C. or less (preferably 70° C. or less) can be mentioned. In addition, as a method for obtaining resin particles having flexibility and low restorability, a method for reducing the degree of crosslinking of the resin used can be mentioned.

[0047] The particle diameter of the resin particles (before compression) can be appropriately set depending on the application. The particle diameter of the resin particles (before compression) is preferably 0.5 μm or more, more preferably 1 μm or more, and preferably 500 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 20 μm or less, and most preferably 10 μm or less. When the particle diameter of the resin particles is the above lower limit or more and the above upper limit or less, the resin particles can be more suitably used for conductive particles and spacers.

[0048] The particle diameter of the resin particles (before compression) is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the resin particles is obtained, for example, by observing 50 arbitrary resin particles with an electron microscope or optical microscope and calculating the average particle diameter of each resin particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each resin particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary resin particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each resin particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the resin particles is preferably calculated using a particle size distribution measuring device.

[0049] In the case of measuring the particle size of the resin particles in the conductive particles, the measurement can be carried out, for example, as follows.

[0050] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, a field emission scanning electron microscope (FE-SEM) is used to set the image magnification to 25,000 times, and 50 conductive particles are randomly selected to observe the resin particles of each conductive particle. The particle diameter of the resin particles in each conductive particle is measured, and the particle diameter of the resin particles is determined by arithmetic averaging.

[0051] The coefficient of variation (CV value) of the particle diameter of the resin particles is preferably 15% or less, more preferably 10% or less, and further preferably 5% or less. When the CV value is equal to or less than the upper limit, the resin particles can be more suitably used for conductive particles and spacers.

[0052] The CV value is expressed by the following formula.

[0053] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of resin particle diameter Dn: average particle size of resin particles

[0054] The shape of the resin particles (before compression) is not particularly limited. The shape of the resin particles (before compression) may be spherical, may be a shape other than spherical, or may be flat or the like.

[0055] The thermal decomposition temperature of the resin particles is preferably 200° C. or higher, more preferably 220° C. or higher, and preferably 350° C. or lower, more preferably 300° C. or lower. When the thermal decomposition temperature of the resin particles is equal to or higher than the lower limit and equal to or lower than the upper limit, the shape of the resin particles after release from compression can be improved, and the effects of the present invention can be more effectively exhibited.

[0056] The thermal decomposition temperature can be measured using a thermogravimetric and differential thermal analyzer (for example, "TG / DTA:STA7200" manufactured by Hitachi High-Tech Science Corp.) 10 mg of the resin particles are heated in air at a rate of 5° C. / min, and the temperature at which the weight is reduced by 10% in the measurement results is defined as the thermal decomposition temperature.

[0057] The compressive elastic modulus (10% K value) when the resin particles are compressed by 10% is preferably 100 N / mm 2 More preferably, 500N / mm 2 More preferably, 1000N / mm 2 More than 3500N / mm 2 Less than or equal to 3200N / mm 2 Less than 2800N / mm 2 When the 10% K value is equal to or more than the above lower limit and equal to or less than the above upper limit, the effects of the present invention can be more effectively exhibited.

[0058] The compressive elastic modulus (30% K value) when the resin particles are compressed by 30% is preferably 100 N / mm 2 More preferably, 300N / mm 2 More preferably, 500N / mm 2 More than 3000N / mm 2 Less than or equal to 2500N / mm 2 Less than 2000N / mm 2 When the 30% K value is equal to or more than the above lower limit and equal to or less than the above upper limit, the effects of the present invention can be more effectively exhibited.

[0059] The compressive elastic modulus (10% K value and 30% K value) of the resin particles can be measured as follows.

[0060] Using a micro-compression tester, one resin particle is compressed with a cylindrical (diameter 50 μm, made of diamond) smooth indenter end face under the conditions of 25° C., compression speed 0.3 mN / sec, and maximum test load 20 mN. The load value (N) and compression displacement (mm) at this time are measured. From the obtained measured value, the compression modulus (10% K value and 30% K value) can be calculated by the following formula. As the micro-compression tester, for example, Fischer Scope H-100 manufactured by Fischer is used. The compression modulus (10% K value and 30% K value) of the resin particle is preferably calculated by arithmetic averaging of the compression modulus (10% K value and 30% K value) of 50 arbitrarily selected resin particles.

[0061] 10%K value and 30%K value (N / mm 2 )=(3 / 2 1 / 2 )·F·S -3 / 2 ·R -1 / 2 F: Load value (N) when resin particles are compressed by 10% or 30% S: Compressive displacement (mm) when the resin particles are compressed by 10% or 30% R: Radius of resin particle (mm)

[0062] The compressive elastic modulus universally and quantitatively represents the hardness of the resin particles. By using the compressive elastic modulus, the hardness of the resin particles can be quantitatively and unambiguously represented.

[0063] The compression recovery rate of the resin particles is preferably 5% or more, more preferably 8% or more, and is preferably 60% or less, more preferably 40% or less. When the compression recovery rate is equal to or more than the lower limit and equal to or less than the upper limit, the effects of the present invention can be more effectively exhibited.

[0064] The compression recovery rate of the resin particles can be measured as follows.

[0065] Resin particles are scattered on a sample stage. A micro-compression tester is used to apply a load (reversed load value) to each scattered resin particle at 25°C toward the center of the resin particle with the smooth end face of a cylinder (diameter 50 μm, made of diamond) until the resin particle is compressed and deformed by 30%. The load is then removed to the load value for the origin (0.40 mN). The load-compression displacement during this period is measured, and the compression recovery rate can be calculated from the following formula. The loading speed is 0.33 mN / sec. For example, a Fischerscope H-100 manufactured by Fischer is used as the micro-compression tester.

[0066] Compression recovery rate (%) = [L2 / L1] x 100 L1: Compressive displacement from the load value for the origin to the load value for the reverse load when applying a load L2: Unloading displacement from the reverse load value when releasing the load to the load value for the origin

[0067] The use of the resin particles is not particularly limited. The resin particles are suitably used for various purposes. By changing the compression conditions of the resin particles during use, the thickness of the resin particles can be suitably changed.

[0068] The resin particles are preferably used as a spacer, an adhesive for electronic components, a conductive particle having a conductive portion, or a material for additive manufacturing. The resin particles are more preferably used as a spacer, an adhesive for electronic components, or a conductive particle having a conductive portion. In the conductive particle, the conductive portion is formed on the surface of the resin particle.

[0069] The resin particles are preferably used in or as a spacer. Examples of the use of the spacer include a spacer for a liquid crystal display element, a spacer for gap control, a spacer for stress relaxation, and a spacer for a light control laminate. The spacer for gap control can be used for gap control of a laminated chip to ensure stand-off height and flatness, and for gap control of an optical component to ensure smoothness of a glass surface and thickness of an adhesive layer. The spacer for stress relaxation can be used for stress relaxation of a sensor chip, etc., and stress relaxation of a connection portion connecting two connection target members. Examples of the sensor chip include a semiconductor sensor chip, etc.

[0070] The resin particles are preferably used as spacers for liquid crystal display elements or as spacers for liquid crystal display elements, and are preferably used as a peripheral sealant for liquid crystal display elements. The resin particles are preferably used as spacers for liquid crystal display elements, as adhesives for electronic components, or for obtaining conductive particles having a conductive portion. In the peripheral sealant for liquid crystal display elements, the resin particles preferably function as spacers. Since the resin particles have good compression deformation characteristics, when the resin particles are used as spacers to be arranged between substrates, or when a conductive portion is formed on the surface and the resin particles are used as conductive particles to electrically connect between electrodes, the spacers or conductive particles are efficiently arranged between the substrates or between the electrodes. Furthermore, the resin particles can suppress the aggregation and movement of the spacers, so that in the liquid crystal display element using the spacers for liquid crystal display elements and the connection structure using the conductive particles, connection failures and display failures are less likely to occur.

[0071] The resin particles are preferably used in or as an adhesive for electronic components. Examples of the adhesive for electronic components include adhesives for liquid crystal panels, adhesives for laminated substrates, adhesives for substrate circuits, and adhesives for camera modules. Examples of the laminated substrate include, for example, semiconductor sensor chips. The resin particles used in the adhesive for electronic components or the resin particles used as the adhesive for electronic components are preferably adhesive resin particles having adhesive properties. When the resin particles are adhesive resin particles, the resin particles and the laminated target member can be well bonded when the resin particles are pressed and hardened. The resin particles can be used alone as an adhesive for electronic components. The resin particles can be used as an adhesive for electronic components without using other adhesive components. When the resin particles are used as an adhesive for electronic components, they do not have to be used alone as an adhesive for electronic components, and may be used together with other adhesive components. In addition, when the resin particles are adhesive resin particles having adhesive properties, they can also be used as a spacer and an adhesive for electronic components. When the above-mentioned resin particles are used as a spacer and adhesive for electronic components, it is possible to more highly achieve a balance between the physical properties required of a spacer, such as gap controllability and stress relaxation properties, and adhesiveness, compared to when the spacer and adhesive are made of different materials.

[0072] The resin particles are preferably used as a material for additive manufacturing. When the resin particles are used as a material for additive manufacturing, for example, the resin particles are three-dimensionally laminated to form a specific shape, and then the resin particles are cured to form a three-dimensional object.

[0073] Other details of the resin particles will be described below. In this specification, "(meth)acrylate" means one or both of "acrylate" and "methacrylate", and "(meth)acrylic" means one or both of "acrylic" and "methacrylic".

[0074] (Other details of resin particles) The material of the resin particles is not particularly limited. The material of the resin particles is preferably an organic material. The resin particles may be particles having a porous structure or may be particles having a solid structure. The porous structure means a structure having a plurality of pores. The solid structure means a structure not having a plurality of pores.

[0075] As shown below, there are various resin particle materials, and in the present invention, a material that can satisfy the above specific compression characteristics is used.

[0076] Examples of the organic material include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, urethane resin, isocyanate resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. Examples of the divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer.

[0077] The material of the resin particles is preferably an epoxy resin, a melamine resin, a benzoguanamine resin, a urethane resin, a isocyanate resin, a polyimide resin, a polyamide resin, a polyamideimide resin, a phenol resin, or a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group. The material of the resin particles is more preferably an epoxy resin, a melamine resin, a benzoguanamine resin, a polyimide resin, a polyamide resin, a polyamideimide resin, a phenol resin, or a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group. The material of the resin particles further preferably includes a thermosetting resin. Examples of the thermosetting resin include epoxy resin, melamine resin, urethane resin, polyimide resin, and phenol resin, but other thermosetting resins may also be used. The material of the resin particles is particularly preferably an epoxy resin. When the material of the resin particles satisfies the above preferred aspects, the compression characteristics of the resin particles can be more easily controlled within a suitable range.

[0078] When an epoxy resin is used as the material of the resin particles, the epoxy resin is preferably a multifunctional epoxy resin. Examples of the epoxy resin include bifunctional epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins, trifunctional epoxy resins such as triazine type epoxy resins and glycidylamine type epoxy resins, and tetrafunctional epoxy resins such as tetrakisphenolethane type epoxy resins and glycidylamine type epoxy resins. The epoxy resins may be used alone or in combination of two or more.

[0079] In addition, when an epoxy resin is used as the material of the resin particles, it is preferable to use a curing agent together with the epoxy resin. The curing agent thermally cures the epoxy resin. The curing agent is not particularly limited. Examples of the curing agent include imidazole curing agents, amine curing agents, phenolic curing agents, thiol curing agents such as polythiol curing agents, and acid anhydride curing agents. The thermal curing agent may be used alone or in combination of two or more. From the viewpoint of easily controlling the compression characteristics of the resin particles to a suitable range, the curing agent is preferably an amine curing agent.

[0080] The imidazole curing agent is not particularly limited. Examples of the imidazole curing agent include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydro Examples of imidazole compounds in which the hydrogen at the 5-position of 1H-imidazole is substituted with a hydroxymethyl group and the hydrogen at the 2-position is substituted with a phenyl group or a toluyl group include 2-phenyl-4-benzyl-5-hydroxymethylimidazole, 2-para-toluyl-4-methyl-5-hydroxymethylimidazole, 2-meta-toluyl-4-methyl-5-hydroxymethylimidazole, 2-meta-toluyl-4,5-dihydroxymethylimidazole, and 2-para-toluyl-4,5-dihydroxymethylimidazole.

[0081] The thiol curing agent is not particularly limited, and examples of the thiol curing agent include trimethylolpropane tris-3-mercaptopropionate, pentaerythritol tetrakis-3-mercaptopropionate, and dipentaerythritol hexa-3-mercaptopropionate.

[0082] The amine curing agent is not particularly limited. Examples of the amine curing agent include ethylenediamine, hexamethylenediamine, octamethylenediamine, decamethylenediamine, 3,9-bis(3-aminopropyl)-2,4,8,10-tetraspiro[5.5]undecane, bis(4-aminocyclohexyl)methane, norbornanediamine, phenylenediamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, metaphenylenediamine, diaminodiphenylmethane, diaminophenylether, metaxylenediamine, diaminonaphthalene, bisaminomethylcyclohexane, and diaminodiphenylsulfone. From the viewpoint of easily controlling the compression characteristics of the resin particles to a suitable range, the amine curing agent is preferably ethylenediamine, hexamethylenediamine, octamethylenediamine, metaphenylenediamine, diaminodiphenylsulfone, phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane. From the viewpoint of easily controlling the compression characteristics of the resin particles within a suitable range, it is more preferable that the amine curing agent is ethylenediamine, norbornanediamine, diaminodiphenylmethane, phenylenediamine, or 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

[0083] The acid anhydride curing agent is not particularly limited, and can be widely used as long as it is an acid anhydride used as a curing agent for thermosetting compounds such as epoxy compounds. Examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, anhydrides of phthalic acid derivatives, maleic anhydride, nadic anhydride, methylnadic anhydride, glutaric anhydride, succinic anhydride, glycerin bistrimellitic anhydride monoacetate, and ethylene glycol bistrimellitic anhydride, bifunctional acid anhydride curing agents such as trimellitic anhydride, trifunctional acid anhydride curing agents such as trimellitic anhydride, and tetrafunctional or more acid anhydride curing agents such as pyromellitic anhydride, benzophenonetetracarboxylic anhydride, methylcyclohexenetetracarboxylic anhydride, and polyazelaic anhydride.

[0084] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.

[0085] Examples of the non-crosslinkable monomer include vinyl compounds such as styrene monomers, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; and (meth)acrylic compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl Examples of suitable (meth)acrylate compounds include alkyl (meth)acrylate compounds such as (meth)acrylate and isobornyl (meth)acrylate; oxygen-containing (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; α-olefin compounds such as diisobutylene, isobutylene, linearne, ethylene, and propylene; and conjugated diene compounds such as isoprene and butadiene.

[0086] Examples of the crosslinkable monomer include vinyl compounds such as vinyl monomers like divinylbenzene, 1,4-divinyloxybutane, and divinylsulfone; and (meth)acrylic compounds such as tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. , dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol Polyfunctional (meth)acrylate compounds such as di(meth)acrylate; allyl compounds such as triallyl (iso)cyanurate, triallyl trimellitate, diallyl phthalate, diallyl acrylamide, and diallyl ether; silane compounds such as silane alkoxide compounds such as tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, and diphenyldimethoxysilane;Examples of the silane alkoxides include silanes containing polymerizable double bonds, such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as one-end modified silicone oil, both-end silicone oil, and side-chain silicone oil; and carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride.

[0087] The resin particles can be obtained by polymerizing the polymerizable monomer having the ethylenically unsaturated group.The polymerization method is not particularly limited, and includes known methods such as radical polymerization, ionic polymerization, polycondensation (condensation polymerization, condensation polymerization), addition condensation, living polymerization, and living radical polymerization.In addition, another polymerization method includes suspension polymerization in the presence of a radical polymerization initiator.

[0088] (Conductive particles) The conductive particles include the above-mentioned resin particles and conductive portions disposed on the surfaces of the resin particles.

[0089] FIG. 2 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.

[0090] 2 has a resin particle 1 and a conductive portion 2 disposed on the surface of the resin particle 1. The conductive portion 2 covers the surface of the resin particle 1. The conductive particle 11 is a coated particle in which the surface of the resin particle 1 is covered with the conductive portion 2.

[0091] FIG. 3 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.

[0092] The conductive particle 21 shown in FIG. 3 has a resin particle 1 and a conductive portion 22 arranged on the surface of the resin particle 1. In the conductive particle 21 shown in FIG. 3, only the conductive portion 22 differs from the conductive particle 11 shown in FIG. 2. The conductive portion 22 has a first conductive portion 22A which is an inner layer and a second conductive portion 22B which is an outer layer. The first conductive portion 22A is arranged on the surface of the resin particle 1. The second conductive portion 22B is arranged on the surface of the first conductive portion 22A.

[0093] FIG. 4 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.

[0094] The conductive particle 31 shown in FIG. 4 includes a resin particle 1, a conductive portion 32, a plurality of core materials 33, and a plurality of insulating materials .

[0095] The conductive portion 32 is disposed on the surface of the resin particle 1. The conductive particle 31 has a plurality of protrusions 31a on its conductive surface. The conductive portion 32 has a plurality of protrusions 32a on its outer surface. In this manner, the conductive particle may have protrusions on the conductive surface of the conductive particle, or may have protrusions on the outer surface of the conductive portion. A plurality of core substances 33 are disposed on the surface of the resin particle 1. The plurality of core substances 33 are embedded in the conductive portion 32. The core substances 33 are disposed inside the protrusions 31a, 32a. The conductive portion 32 covers the plurality of core substances 33. The outer surface of the conductive portion 32 is raised by the plurality of core substances 33, forming the protrusions 31a, 32a.

[0096] The conductive particle 31 has an insulating material 34 disposed on the outer surface of the conductive portion 32. At least a portion of the outer surface of the conductive portion 32 is covered with the insulating material 34. The insulating material 34 is made of a material having insulating properties, and is an insulating particle. In this manner, the conductive particle may have an insulating material disposed on the outer surface of the conductive portion.

[0097] The metal for forming the conductive portion is not particularly limited. Examples of the metal include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. Examples of the metal include tin-doped indium oxide (ITO) and solder. From the viewpoint of further increasing the connection reliability between electrodes, the metal is preferably an alloy containing tin, nickel, palladium, copper, or gold, and is preferably nickel or palladium.

[0098] The conductive part may be formed of one layer, as in the conductive particles 11 and 31. The conductive part may be formed of multiple layers, as in the conductive particle 21. That is, the conductive part may have a laminated structure of two or more layers. When the conductive part is formed of multiple layers, the outermost layer is preferably a gold layer, a nickel layer, a palladium layer, a copper layer, or an alloy layer containing tin and silver, and more preferably a gold layer. When the outermost layer is one of these preferred conductive parts, the connection reliability between the electrodes can be further improved. In addition, when the outermost layer is a gold layer, the corrosion resistance can be further improved.

[0099] The method of forming the conductive part on the surface of the resin particle is not particularly limited. The method of forming the conductive part includes electroless plating, electroplating, physical vapor deposition, and coating the surface of the resin particle with a metal powder or a paste containing a metal powder and a binder. From the viewpoint of forming the conductive part more easily, the electroless plating method is preferred. The physical vapor deposition method includes vacuum deposition, ion plating, ion sputtering, and the like.

[0100] The compressive elastic modulus (10% K value) of the conductive particles when compressed by 10% is preferably 1000 N / mm 2 More preferably, 3000N / mm 2More preferably, 4500N / mm 2 More than 10000N / mm 2 Less than or equal to 9000N / mm 2 Less than 8000N / mm 2 When the 10% K value is equal to or more than the above lower limit and equal to or less than the above upper limit, the effects of the present invention can be more effectively exhibited.

[0101] The compressive elastic modulus (30% K value) when the conductive particles are compressed by 30% is preferably 1000 N / mm 2 More preferably, 3000N / mm 2 More preferably, 4500N / mm 2 More than 10000N / mm 2 Less than or equal to 8000N / mm 2 Less than 6000N / mm 2 When the 30% K value is equal to or more than the above lower limit and equal to or less than the above upper limit, the effects of the present invention can be more effectively exhibited.

[0102] The compressive elastic modulus (10% K value and 30% K value) of the conductive particles can be measured in the same manner as the compressive elastic modulus (10% K value and 30% K value) of the resin particles.

[0103] The compressive elastic modulus universally and quantitatively represents the hardness of the conductive particles. By using the compressive elastic modulus, the hardness of the conductive particles can be quantitatively and unambiguously represented.

[0104] The compression recovery rate of the conductive particles is preferably 5% or more, more preferably 8% or more, and is preferably 60% or less, more preferably 40% or less. When the compression recovery rate is equal to or more than the lower limit and equal to or less than the upper limit, the effects of the present invention can be more effectively exhibited.

[0105] The compression recovery rate of the conductive particles can be measured in the same manner as the compression recovery rate of the resin particles.

[0106] The particle diameter of the conductive particles is preferably 0.5 μm or more, more preferably 1.0 μm or more, and preferably 500 μm or less, more preferably 450 μm or less, even more preferably 100 μm or less, even more preferably 50 μm or less, and particularly preferably 20 μm or less. If the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, when electrodes are connected using the conductive particles, the contact area between the conductive particles and the electrodes becomes sufficiently large, and the conductive particles are less likely to be aggregated when forming the conductive part. In addition, the gap between the electrodes connected via the conductive particles does not become too large, and the conductive part is less likely to peel off from the surface of the resin particles. In addition, if the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, the conductive particles can be suitably used for conductive material applications.

[0107] The particle diameter of the conductive particles means the diameter when the conductive particles are spherical, and means the diameter when the conductive particles are other than spherical, assuming that the conductive particles are a true sphere of equivalent volume.

[0108] The particle diameter of the conductive particles is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the conductive particles is obtained by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope, calculating an average value, or by performing laser diffraction particle size distribution measurement. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the laser diffraction particle size distribution measurement, the particle diameter of each conductive particle is obtained as a particle diameter of a sphere equivalent diameter. The particle diameter of the conductive particles is preferably calculated by laser diffraction particle size distribution measurement.

[0109] The thickness of the conductive part is preferably 0.005 μm or more, more preferably 0.01 μm or more, and preferably 10 μm or less, more preferably 1 μm or less, and even more preferably 0.3 μm or less. The thickness of the conductive part is the thickness of the entire conductive part when the conductive part is multi-layered. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity is obtained, and the conductive particles do not become too hard, so that the conductive particles are sufficiently deformed when connecting between electrodes.

[0110] When the conductive part is formed of a plurality of layers, the thickness of the conductive part of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, and preferably 0.5 μm or less, more preferably 0.1 μm or less. When the thickness of the conductive part of the outermost layer is equal to or more than the lower limit and equal to or less than the upper limit, the coating by the conductive part of the outermost layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection reliability between the electrodes can be further improved. In addition, when the outermost layer is a gold layer, the thinner the gold layer, the lower the cost.

[0111] The thickness of the conductive part can be measured by observing the cross section of the conductive particle using, for example, a transmission electron microscope (TEM). The thickness of the conductive part is preferably calculated as the thickness of the conductive part of one conductive particle by averaging the thicknesses of five arbitrary conductive parts, and more preferably calculated as the thickness of the conductive part of one conductive particle by averaging the thickness of the entire conductive part. The thickness of the conductive part is preferably determined by calculating the average thickness of the conductive part of each of 50 arbitrary conductive particles.

[0112] The conductive particles preferably have protrusions on the outer surface of the conductive part. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is often formed on the surface of the conductive part and the surface of the electrode connected by the conductive particles. When conductive particles having protrusions are used, the oxide film is effectively removed by the protrusions by arranging the conductive particles between the electrodes and pressing them together. Therefore, the electrodes and the conductive parts of the conductive particles can be more reliably contacted, and the connection resistance between the electrodes can be further reduced. Furthermore, when the conductive particles have an insulating material on their surfaces, or when the conductive particles are dispersed in a binder resin and used as a conductive material, the insulating material or binder resin between the conductive particles and the electrodes can be more effectively removed by the protrusions of the conductive particles. Therefore, the connection reliability between the electrodes can be further improved.

[0113] The method for forming protrusions on the surface of the conductive particles includes a method of adhering a core material to the surface of a resin particle and then forming a conductive part by electroless plating, and a method of forming a conductive part on the surface of a resin particle by electroless plating, adhering a core material, and further forming a conductive part by electroless plating, etc. Also, the core material does not have to be used to form the protrusions.

[0114] Methods for forming the above-mentioned protrusions include the following: A method of adding a core substance at an intermediate stage of forming a conductive part on the surface of a resin particle by electroless plating. A method for forming protrusions by electroless plating without using a core substance includes generating metal nuclei by electroless plating, attaching the metal nuclei to the surface of a resin particle or a conductive part, and further forming a conductive part by electroless plating.

[0115] The conductive particles preferably further comprise an insulating material disposed on the outer surface of the conductive portion. In this case, when the conductive particles are used for connection between electrodes, short-circuiting between adjacent electrodes can be prevented. Specifically, when a plurality of conductive particles contact each other, an insulating material exists between the plurality of electrodes, so that short-circuiting between electrodes adjacent in the horizontal direction, rather than between upper and lower electrodes, can be prevented. In addition, when connecting between electrodes, the insulating material between the conductive portion of the conductive particle and the electrode can be easily removed by pressing the conductive particle with two electrodes. When the conductive particle has a protrusion on the surface of the conductive portion, the insulating material between the conductive portion of the conductive particle and the electrode can be more easily removed. The insulating material is preferably an insulating resin layer or insulating particles, more preferably insulating particles. The insulating particles are preferably insulating resin particles.

[0116] The outer surface of the conductive part and the surface of the insulating particle may each be coated with a compound having a reactive functional group. The outer surface of the conductive part and the surface of the insulating particle may not be directly chemically bonded, and may be indirectly chemically bonded by a compound having a reactive functional group. After introducing a carboxyl group into the outer surface of the conductive part, the carboxyl group may be chemically bonded to the functional group on the surface of the insulating particle via a polymer electrolyte such as polyethyleneimine.

[0117] (Conductive materials) The conductive material includes the conductive particles and a binder resin. The conductive particles are preferably dispersed in the binder resin and used as the conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection of electrodes. The conductive material is preferably a circuit connection material.

[0118] The binder resin is not particularly limited. As the binder resin, a known insulating resin is used. The binder resin preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. The curable component includes a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent. Examples of the binder resin include a vinyl resin, a thermoplastic resin, a curable resin, a thermoplastic block copolymer, and an elastomer. Only one type of the binder resin may be used, or two or more types may be used in combination.

[0119] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.

[0120] In addition to the conductive particles and the binder resin, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.

[0121] The method for dispersing the conductive particles in the binder resin is not particularly limited and may be a conventionally known dispersion method. Examples of the method for dispersing the conductive particles in the binder resin include the following methods. A method in which the conductive particles are added to the binder resin and then kneaded and dispersed with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, then added to the binder resin, and then kneaded and dispersed with a planetary mixer or the like. A method in which the binder resin is diluted with water or an organic solvent, then the conductive particles are added, and then kneaded and dispersed with a planetary mixer or the like.

[0122] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is equal to or more than the lower limit and equal to or less than the upper limit, the connection reliability between electrodes can be more effectively improved. The viscosity (η25) can be appropriately adjusted by the types and amounts of the components.

[0123] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.

[0124] The conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material according to the present invention is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0125] In 100% by weight of the conductive material, the content of the binder resin is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder resin is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged between the electrodes, and the connection reliability of the connection target members connected by the conductive material is further increased.

[0126] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, even more preferably 20% by weight or less, and particularly preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced, and the connection reliability between the electrodes can be more effectively increased.

[0127] (Connection structure) A connection structure can be obtained by connecting members to be connected using the above-mentioned resin particles.

[0128] The connection structure using the resin particles includes a first connection target member, a second connection target member, and a connection part connecting the first connection target member and the second connection target member. In the connection structure, the connection part is formed from the resin particles or a composition containing the resin particles. In the connection structure using the resin particles, it is preferable that the resin particles are in direct contact with the first connection target member and the second connection target member.

[0129] A connection structure can be obtained by connecting members to be connected using the above-mentioned conductive particles or a conductive material containing the above-mentioned conductive particles and a binder resin.

[0130] The connection structure using the conductive particles includes a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part connecting the first connection target member and the second connection target member. In the connection structure, the connection part is formed of conductive particles or is formed of a conductive material containing the conductive particles and a binder resin. The conductive particles include the above-mentioned resin particles and a conductive part disposed on the surface of the resin particles. In the connection structure, the first electrode and the second electrode are electrically connected by the conductive particles.

[0131] When the conductive particles are used alone, the connection part itself is a conductive particle. That is, the first connection target member and the second connection target member are connected by the conductive particles. The conductive material used to obtain the connection structure is preferably an anisotropic conductive material.

[0132] FIG. 5 is a cross-sectional view showing an example of a connection structure using conductive particles according to the first embodiment of the present invention.

[0133] The connection structure 41 shown in Fig. 5 includes a first connection target member 42, a second connection target member 43, and a connection portion 44 connecting the first connection target member 42 and the second connection target member 43. The connection portion 44 is formed of a conductive material including conductive particles 11 and a binder resin. In Fig. 5, the conductive particles 11 are shown in a simplified diagram for convenience of illustration. Instead of the conductive particles 11, conductive particles other than the conductive particles 21 and 31 may be used.

[0134] The first connection target member 42 has a plurality of first electrodes 42a on its surface (upper surface). The second connection target member 43 has a plurality of second electrodes 43a on its surface (lower surface). The first electrodes 42a and the second electrodes 43a are electrically connected by one or more conductive particles 11. Therefore, the first and second connection target members 42 and 43 are electrically connected by the conductive particles 11.

[0135] The method for producing the connection structure is not particularly limited. One example of the method for producing the connection structure is a method in which the conductive material is placed between a first connection target member and a second connection target member, a laminate is obtained, and then the laminate is heated and pressurized. The pressure during the pressurization is preferably 40 MPa or more, more preferably 60 MPa or more, and preferably 90 MPa or less, more preferably 70 MPa or less. The temperature during the heating is preferably 80°C or more, more preferably 100°C or more, and preferably 140°C or less, more preferably 120°C or less.

[0136] The first and second connection target members are not particularly limited. Specific examples of the first and second connection target members include electronic components such as semiconductor chips, semiconductor packages, LED chips, LED packages, capacitors, and diodes, as well as electronic components such as resin films, printed circuit boards, flexible printed circuit boards, flexible flat cables, rigid flexible boards, glass epoxy boards, and glass boards. The first and second connection target members are preferably electronic components.

[0137] The conductive material is preferably a conductive material for connecting electronic components. The conductive paste is preferably a conductive material in a paste form, and is preferably applied in a paste form onto the connection target members.

[0138] The conductive particles, the conductive material and the connection material are also suitable for use in touch panels. Therefore, the connection target member is preferably a flexible substrate or a connection target member having electrodes arranged on the surface of a resin film. The connection target member is preferably a flexible substrate, and is preferably a connection target member having electrodes arranged on the surface of a resin film. When the flexible substrate is a flexible printed circuit board or the like, the flexible substrate generally has electrodes on its surface.

[0139] Examples of the electrodes provided on the connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the connection target members are flexible printed circuit boards, the electrodes are preferably gold electrodes, nickel electrodes, tin electrodes, silver electrodes, or copper electrodes. When the connection target members are glass substrates, the electrodes are preferably aluminum electrodes, copper electrodes, molybdenum electrodes, or tungsten electrodes. When the electrodes are aluminum electrodes, they may be electrodes made of aluminum only, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.

[0140] The resin particles can be suitably used as a spacer for a liquid crystal display element. The first connection target member may be a first member for a liquid crystal display element. The second connection target member may be a second member for a liquid crystal display element. The connection portion may be a seal portion that seals the outer periphery of the first member for a liquid crystal display element and the second member for a liquid crystal display element in a state in which the first member for a liquid crystal display element and the second member for a liquid crystal display element face each other.

[0141] The resin particles can also be used in a peripheral sealant for liquid crystal display elements. The liquid crystal display element includes a first member for liquid crystal display elements and a second member for liquid crystal display elements. The liquid crystal display element further includes a seal part that seals the outer periphery of the first member for liquid crystal display elements and the second member for liquid crystal display elements in a state in which the first member for liquid crystal display elements and the second member for liquid crystal display elements face each other, and liquid crystal disposed inside the seal part between the first member for liquid crystal display elements and the second member for liquid crystal display elements. In this liquid crystal display element, a liquid crystal dropping method is applied, and the seal part is formed by thermally curing a sealant for the liquid crystal dropping method.

[0142] The above liquid crystal display element is 1 mm 2 The arrangement density of the spacers for the liquid crystal display element per unit area is preferably 10 pieces / mm 2 or more, and preferably 1000 pieces / mm 2 The above arrangement density is 10 pieces / mm 2 When the arrangement density is 1000 pieces / mm or more, the cell gap becomes more uniform. 2 When the thickness is equal to or less than this, the contrast of the liquid crystal display element becomes even better.

[0143] (Electronic component equipment) The above-mentioned resin particles or conductive particles can be disposed between the first ceramic member and the second ceramic member on the outer periphery of the first ceramic member and the second ceramic member, and can also be used as a gap control material and a conductive connecting material.

[0144] Fig. 6 is a cross-sectional view showing an example of an electronic component device using the resin particles according to the present invention, Fig. 7 is a cross-sectional view showing an enlarged joint portion of the electronic component device shown in Fig. 6.

[0145] An electronic component device 81 shown in FIGS. 6 and 7 includes a first ceramic member 82, a second ceramic member 83, a joint portion 84, an electronic component 85, and a lead frame 86.

[0146] The first and second ceramic members 82 and 83 are each formed of a ceramic material. The first and second ceramic members 82 and 83 are each, for example, a housing. The first ceramic member 82 is, for example, a substrate. The second ceramic member 83 is, for example, a lid. The first ceramic member 82 has a convex portion protruding toward the second ceramic member 83 side (upper side) on the outer periphery. The first ceramic member 82 has a concave portion on the second ceramic member 83 side (upper side) that forms an internal space R for accommodating an electronic component 85. The first ceramic member 82 may not have a convex portion. The second ceramic member 83 has a convex portion protruding toward the first ceramic member 82 side (lower side) on the outer periphery. The second ceramic member 83 has a concave portion on the first ceramic member 82 side (lower side) that forms an internal space R for accommodating an electronic component 85. The second ceramic member 83 may not have a convex portion. The first ceramic member 82 and the second ceramic member 83 form an internal space R.

[0147] The bonding portion 84 bonds an outer periphery of the first ceramic member 82 to an outer periphery of the second ceramic member 83. Specifically, the bonding portion 84 bonds a convex portion of the outer periphery of the first ceramic member 82 to a convex portion of the outer periphery of the second ceramic member 83.

[0148] A package is formed by first and second ceramic members 82, 83 joined by a joint 84. An internal space R is formed by the package. The joint 84 seals the internal space R liquid-tightly and air-tightly. The joint 84 is a sealing portion.

[0149] The electronic component 85 is disposed in the internal space R of the package. Specifically, the electronic component 85 is disposed on the first ceramic member 82. In this embodiment, two electronic components 85 are used.

[0150] The bonding portion 84 includes a plurality of resin particles 1 and glass 84B. The bonding portion 84 is formed using a bonding material including a plurality of resin particles 1 different from glass particles and glass 84B. This bonding material is a bonding material for ceramic packages. The bonding material may include the conductive particles described above instead of the resin particles.

[0151] The bonding material may contain a solvent or may contain a resin. In the bonding portion 84, glass 84B such as glass particles is melted and bonded, and then solidified.

[0152] Examples of the electronic components include sensor elements, MEMS, bare chips, etc. Examples of the sensor elements include pressure sensor elements, acceleration sensor elements, CMOS sensor elements, CCD sensor elements, and housings for the above various sensor elements.

[0153] Lead frame 86 is disposed between the outer periphery of first ceramic member 82 and the outer periphery of second ceramic member 83. Lead frame 86 extends to the internal space R side and the external space side of the package. Terminals of electronic component 85 and lead frame 86 are electrically connected via wires.

[0154] The joint 84 partially directly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83, and partially indirectly joins them. Specifically, the joint 84 indirectly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83 via the lead frame 86 in a portion where the lead frame 86 is present between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83. In a portion where the lead frame 86 is present between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83, the first ceramic member 82 is in contact with the lead frame 86, and the lead frame 86 is in contact with the first ceramic member 82 and the joint 84. Furthermore, the joint 84 is in contact with the lead frame 86 and the second ceramic member 83, and the second ceramic member 83 is in contact with the joint 84. The joint 84 directly joins the outer periphery of the first ceramic member 82 to the outer periphery of the second ceramic member 83 in a portion where there is no lead frame 86 between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83. The joint 84 contacts the first ceramic member 82 and the second ceramic member 83 in a portion where there is no lead frame 86 between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83.

[0155] In the portion where the lead frame 86 is located between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83, the distance of the gap between the outer periphery of the first ceramic member 82 and the outer periphery of the second ceramic member 83 is controlled by multiple resin particles 1 contained in the bonding portion 84.

[0156] The bonding portion may be any portion that directly or indirectly bonds the outer periphery of the first ceramic member to the outer periphery of the second ceramic member, and an electrical connection method other than the use of a lead frame may also be used.

[0157] Like the electronic component device 81, the electronic component device may include, for example, a first ceramic member formed of a ceramic material, a second ceramic member formed of a ceramic material, a joint, and an electronic component. In the electronic component device, the joint may directly or indirectly join an outer periphery of the first ceramic member to an outer periphery of the second ceramic member. In the electronic component device, a package may be formed by the first and second ceramic members joined by the joint. In the electronic component device, the electronic component may be disposed in an internal space of the package, and the joint may include a plurality of resin particles and glass.

[0158] Also, like the bonding material used in the electronic component device 81, the ceramic package bonding material is used to form the bonding portion in the electronic component device and contains resin particles and glass. Note that an electrical connection method that contains only resin particles and does not contain glass may be adopted. The bonding portion may contain the conductive particles described above instead of the resin particles.

[0159] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0160] Example 1 (1) Preparation of resin particles In a reaction vessel equipped with a thermometer, a stirrer, and a cooling tube, 15 parts by weight of bisphenol A type epoxy resin (DIC Corporation "EXA-850-CRP"), 7.5 parts by weight of polyvinylpyrrolidone as a dispersion stabilizer, and 250 parts by weight of ethanol were added and uniformly dissolved by stirring at 68°C for 1 hour. Next, 4.25 parts by weight of 4,4'-diaminodiphenylmethane and 35 parts by weight of ethanol were added and uniformly dissolved, and then added to the reaction vessel and reacted at 68°C for 20 hours to obtain a reaction product. The obtained reaction product was washed and dried to obtain resin particles.

[0161] (2) Preparation of conductive particles 10 parts by weight of the obtained resin particles were dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, and the solution was filtered to extract the resin particles. Next, the resin particles were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surfaces of the resin particles. The resin particles with the activated surfaces were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed to obtain a dispersion.

[0162] In addition, a nickel plating solution (pH 8.5) containing 0.35 mol / L of nickel sulfate, 1.38 mol / L of dimethylamine borane, and 0.5 mol / L of sodium citrate was prepared.

[0163] The nickel plating solution was gradually added dropwise to the obtained dispersion while stirring the dispersion at 60° C., to perform electroless nickel plating. The dispersion was then filtered to extract the particles, which were then washed with water and dried to form a nickel-boron conductive layer on the surface of the resin particles, thereby obtaining conductive particles having a conductive portion on the surface.

[0164] (3) Preparation of conductive material (anisotropic conductive paste) 7 parts by weight of the obtained conductive particles, 25 parts by weight of bisphenol A type phenoxy resin, 4 parts by weight of fluorene type epoxy resin, 30 parts by weight of phenol novolac type epoxy resin, and SI-60L (manufactured by Sanshin Chemical Industry Co., Ltd.) were mixed together, and the mixture was degassed and stirred for 3 minutes to obtain a conductive material (anisotropic conductive paste).

[0165] (4) Fabrication of connection structure A transparent glass substrate (first connection target member) was prepared on the upper surface of which was an IZO electrode pattern (first electrode, Vickers hardness of metal on the electrode surface 100Hv) with L / S of 10μm / 10μm. A semiconductor chip (second connection target member) was prepared on the lower surface of which was an Au electrode pattern (second electrode, Vickers hardness of metal on the electrode surface 50Hv) with L / S of 10μm / 10μm. The obtained anisotropic conductive paste was applied to the transparent glass substrate to a thickness of 30μm to form an anisotropic conductive paste layer. Next, the semiconductor chip was laminated on the anisotropic conductive paste layer so that the electrodes faced each other. Thereafter, a pressurized heating head was placed on the upper surface of the semiconductor chip while adjusting the temperature of the head so that the temperature of the anisotropic conductive paste layer was 100℃, and a pressure of 55MPa was applied to harden the anisotropic conductive paste layer at 100℃, thereby obtaining a connection structure.

[0166] Example 2 When preparing the resin particles, a glycidylamine type epoxy resin ("TETRAD-X" manufactured by Mitsubishi Gas Chemical Company, Inc.) was used instead of the bisphenol A type epoxy resin, and isopropyl alcohol was used instead of ethanol. In addition, the amount of 4,4'-diaminodiphenylmethane blended when preparing the resin particles was changed to 7.53 parts by weight. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0167] Example 3 When preparing the resin particles, a triazine type epoxy resin ("TEPIC-PAS" manufactured by Nissan Chemical Industries, Ltd.) was used instead of a bisphenol A type epoxy resin. In addition, when preparing the resin particles, 1.63 parts by weight of ethylenediamine was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0168] Example 4 When preparing the resin particles, a glycidylamine type epoxy resin ("JER-630" manufactured by Mitsubishi Chemical Corporation) was used instead of a bisphenol A type epoxy resin. In addition, the amount of 4,4'-diaminodiphenylmethane blended when preparing the resin particles was changed to 7.63 parts by weight. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0169] Example 5 When preparing the resin particles, an alicyclic glycidylamine type epoxy resin ("TETRAD-C" manufactured by Mitsubishi Gas Chemical Company, Inc.) was used instead of the bisphenol A type epoxy resin, and isopropyl alcohol was used instead of ethanol. In addition, the amount of 4,4'-diaminodiphenylmethane blended when preparing the resin particles was changed to 7.44 parts by weight. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0170] Example 6 Resin particles were obtained in the same manner as in Example 1. When preparing the conductive particles, 1 g of nickel particle slurry (average particle diameter 100 nm) was added to the dispersion liquid over a period of 3 minutes to obtain a suspension containing resin particles to which a core substance was attached. Conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1, except that the above suspension was used instead of the above dispersion liquid.

[0171] Example 7 (1) Preparation of insulating particles The following monomer composition was placed in a 1000 mL separable flask equipped with a four-neck separable cover, stirring blade, three-way cock, cooling tube and temperature probe, and then distilled water was added so that the solid content of the following monomer composition was 10% by weight, and the mixture was stirred at 200 rpm and polymerized at 60°C for 24 hours under a nitrogen atmosphere. The monomer composition contains 360 mmol of methyl methacrylate, 45 mmol of glycidyl methacrylate, 20 mmol of parastyryldiethylphosphine, 13 mmol of ethylene glycol dimethacrylate, 0.5 mmol of polyvinylpyrrolidone, and 1 mmol of 2,2'-azobis{2-[N-(2-carboxyethyl)amidino]propane}. After the reaction was completed, the mixture was freeze-dried to obtain insulating particles (particle diameter 360 nm) having phosphorus atoms derived from parastyryldiethylphosphine on the surface.

[0172] (2) Preparation of conductive particles with insulating particles The conductive particles obtained in Example 6 were prepared. The insulating particles obtained above were dispersed in distilled water under ultrasonic irradiation to obtain a 10 wt% aqueous dispersion of insulating particles. 10 g of the prepared conductive particles were dispersed in 500 mL of distilled water, and 1 g of the 10 wt% aqueous dispersion of insulating particles was added and stirred at room temperature for 8 hours. After filtering with a 3 μm mesh filter, the mixture was further washed with methanol and dried to obtain conductive particles with insulating particles. A conductive material and a connection structure were obtained in the same manner as in Example 1, except that the conductive particles with insulating particles were used instead of the conductive particles.

[0173] ( reference Example 8) Polystyrene particles with an average particle size of 0.93 μm were prepared as seed particles. 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion-exchanged water, and 120 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol were mixed to prepare a mixed liquid. The mixed liquid was dispersed by ultrasonic waves, then placed in a separable flask and stirred uniformly.

[0174] Next, 2 parts by weight of 2,2'-azobis(methyl isobutyrate) ("V-601" manufactured by Wako Pure Chemical Industries, Ltd.) and 2 parts by weight of benzoyl peroxide ("Niper BW" manufactured by NOF Corp.) were mixed. R An emulsion was prepared by adding 120 parts by weight of diethyl ether diacrylate, 30 parts by weight of styrene, 9 parts by weight of triethanolamine lauryl sulfate, 30 parts by weight of ethanol, and 1100 parts by weight of ion-exchanged water.

[0175] The above emulsion was added in several portions to the above mixture in the separable flask, and the mixture was stirred for 12 hours to allow the seed particles to absorb the monomer, thereby obtaining a suspension containing seed particles swollen with the monomer.

[0176] Thereafter, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, and heating was started to carry out a reaction at 85° C. for 9 hours to obtain resin particles.

[0177] Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained resin particles were used.

[0178] Example 9 When preparing the resin particles, 2.34 parts by weight of 1,4-phenylenediamine was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. Other than the above changes, the resin particles, conductive particles, conductive material, and connection structure were obtained in the same manner as in Example 1.

[0179] Example 10 When preparing the resin particles, 8.90 parts by weight of 2,2-bis[4-(4-aminophenoxy)phenyl]propane was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0180] Example 11 When preparing the resin particles, the amount of 4,4'-diaminodiphenylmethane was changed from 4.25 parts by weight to 8.50 parts by weight. In addition, the stirring at 68°C for 1 hour was changed to stirring at 78°C for 1 hour. In addition, the reaction conditions of 68°C and 20 hours were changed to reaction conditions of 78°C and 20 hours. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0181] Example 12 When preparing the resin particles, 0.80 parts by weight of norbornanediamine was used instead of 4.25 parts by weight of 4,4'-diaminodiphenylmethane. In addition, stirring at 68°C for 1 hour was changed to stirring at 45°C for 1 hour. In addition, the reaction conditions of 68°C and 20 hours were changed to reaction conditions of 45°C and 20 hours. Other than the above changes, the resin particles, conductive particles, conductive materials, and connection structures were obtained in the same manner as in Example 1.

[0182] Comparative Example 1 Polystyrene particles with an average particle size of 0.93 μm were prepared as seed particles. 3.9 parts by weight of the polystyrene particles, 500 parts by weight of ion-exchanged water, and 120 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol were mixed to prepare a mixed liquid. The mixed liquid was dispersed by ultrasonic waves, then placed in a separable flask and stirred uniformly.

[0183] Next, 2 parts by weight of 2,2'-azobis(methyl isobutyrate) (Wako Pure Chemical Industries, Ltd., "V-601") and 2 parts by weight of benzoyl peroxide (NOF Corporation, "Niper BW") were mixed, and 150 parts by weight of divinylbenzene, 9 parts by weight of triethanolamine lauryl sulfate, 30 parts by weight of ethanol, and 1100 parts by weight of ion-exchanged water were added to prepare an emulsion.

[0184] The above emulsion was added in several portions to the above mixture in the separable flask, and the mixture was stirred for 12 hours to allow the seed particles to absorb the monomer, thereby obtaining a suspension containing seed particles swollen with the monomer.

[0185] Thereafter, 490 parts by weight of a 5% by weight aqueous solution of polyvinyl alcohol was added, and heating was started to carry out a reaction at 85° C. for 9 hours to obtain resin particles.

[0186] Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the obtained resin particles were used.

[0187] Comparative Example 2 Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Comparative Example 1, except that 30 parts by weight of 1,6-hexanediol dimethacrylate and 120 parts by weight of styrene were used instead of 150 parts by weight of divinylbenzene.

[0188] Comparative Example 3 As the resin particles, "Optbeads 3500M" manufactured by Nissan Chemical Industries, Ltd. was prepared. Conductive particles, a conductive material, and a connection structure were obtained in the same manner as in Example 1, except that the prepared resin particles were used.

[0189] (evaluation) (1) Particle size (number average particle size) of resin particles and CV value of particle size of resin particles The particle diameters of about 100,000 resin particles obtained were measured using a particle size distribution measuring device (Multisizer 4 manufactured by Beckman Coulter, Inc.) and the average value was calculated. From the measurement results of the particle diameters of the resin particles, the CV value of the particle diameters of the resin particles was calculated according to the following formula.

[0190] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of resin particle diameter Dn: average particle size of resin particles

[0191] (2) Aspect ratio of resin particles The obtained resin particles were observed under an electron microscope to determine the aspect ratio, which was determined by averaging the aspect ratios of 50 randomly selected resin particles.

[0192] (3) Shape of resin particles after compression and release A first plate and a second plate made of glass were prepared. Each of the first plate and the second plate had a flat surface. A polyimide film having a thickness of 70% of the particle diameter of the resin particles was attached to the end of the surface of the first plate as a gap material. The first plate and the second plate were heated so that the surface temperature of the first plate and the second plate reached 200°C, and the obtained resin particles were placed on the surface of the heated first plate. Within 3 to 5 minutes after the resin particles were placed, the first plate or the second plate was moved to a position where the distance between the first plate and the second plate was 70% of the particle diameter (number average particle diameter) of the resin particles using a vice heat press digital ("MNP2-002D" manufactured by AS ONE Corporation). That is, the resin particles were compressed by 30% with respect to the particle diameter (number average particle diameter). The compression conditions were a compression speed of 2000 mN / sec and a load of 20000 mN. The resin particles were compressed by 30% and held at 200°C for 10 minutes under a load of 20,000 mN, and then released from compression. The resin particles after release were left to stand for 1 hour at 25°C under windless conditions, and then photographed with an electron microscope.

[0193] From the obtained micrographs, it was confirmed whether or not the resin particles after release from compression, observed from a direction perpendicular to the compression direction, had two flat surfaces facing each other in the compression direction.

[0194] In addition, when the resin particle after release from compression has two flat surfaces facing each other in the compression direction, the ratio (A / B) of the major axis A of the flat surface of the resin particle after release from compression to the maximum axis B of the resin particle after release from compression was determined. The ratio (A / B) was calculated by averaging the ratios (A / B) of 50 random resin particles.

[0195] (4) Thermal decomposition temperature The thermal decomposition temperature of the obtained resin particles was measured using a thermogravimetric differential thermal analyzer (Hitachi High-Tech Science Corporation, "TG / DTA:STA7200") The thermal decomposition temperature was measured when 10 mg of the resin particles was heated in air at 5°C / min and the weight of the particles decreased by 10%.

[0196] (5) 10% K value and 30% K value The compressive elastic modulus of the obtained resin particles when compressed by 10% (10% K value) and when compressed by 30% (30% K value), as well as the compressive elastic modulus of the obtained conductive particles when compressed by 10% (10% K value) and when compressed by 30% (30% K value) were measured by the above-mentioned method. Note that the microcompression tester used was Fischer Scope H-100 manufactured by Fischer.

[0197] (6) Thickness of conductive part The obtained conductive particles were added to Kulzer's "Technovit 4000" so that the content was 30% by weight, and dispersed to prepare an embedding resin for testing. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the embedding resin for testing.

[0198] Then, using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.), the image magnification was set to 50,000 times, 50 conductive particles were randomly selected, and the conductive part of each conductive particle was observed. The thickness of the conductive part of each conductive particle was measured, and the arithmetic average was calculated to obtain the thickness of the conductive part.

[0199] (7) Adhesion between resin particles and conductive parts The conductive particles in the connection of the obtained connection structure were observed using a scanning electron microscope ("Regulus8220" manufactured by Hitachi High-Technologies Corporation). For 100 conductive particles observed, it was confirmed whether the conductive part arranged on the surface of the resin particle was peeled off or not. The adhesion between the resin particle and the conductive part was evaluated according to the following criteria.

[0200] [Criteria for determining adhesion between resin particles and conductive parts] ○○○: 0 conductive particles peeled off from the conductive part ○○: The number of conductive particles peeled off from the conductive part is more than 0 and 15 or less ○: More than 15 conductive particles peeled off from the conductive part, but not exceeding 30 △: More than 30 conductive particles peeled off from the conductive part and 50 or less ×: More than 50 conductive particles peeled off from the conductive part

[0201] (8) Shape retention properties of conductive particles The conductive particles in the connection of the obtained connection structure were observed using a scanning electron microscope ("Regulus8220" manufactured by Hitachi High-Technologies Corporation). It was confirmed whether or not the compressed shape was maintained for 100 conductive particles observed. The shape retention property of the conductive particles was evaluated according to the following criteria.

[0202] [Criteria for determining shape retention properties of conductive particles] ○○○: The number of conductive particles that maintain their compressed shape is 90 or more XX: The number of conductive particles that maintain their compressed shape is between 70 and 90 ○: The number of conductive particles that maintain their compressed shape is 50 or more and less than 70 △: The number of conductive particles that maintain their compressed shape is 1 or more and less than 50 ×: The conductive particles do not maintain the compressed shape or are destroyed.

[0203] (9) Connection reliability (between upper and lower electrodes) The connection resistance between the upper and lower electrodes of the 20 connection structures obtained was measured by the four-terminal method. The average connection resistance was calculated. Note that, based on the relationship of voltage = current x resistance, the connection resistance can be calculated by measuring the voltage when a constant current is passed. The connection reliability was evaluated according to the following criteria.

[0204] [Connection reliability criteria] ○○○: The average connection resistance is 1.5Ω or less ○○: The average connection resistance is over 1.5Ω and 2.0Ω or less ○: The average connection resistance is greater than 2.0Ω and less than 5.0Ω △: The average connection resistance is over 5.0Ω and 10Ω or less ×: The average connection resistance exceeds 10 Ω

[0205] (10) Impact resistance Twenty of the resulting connection structures were dropped from a height of 70 cm, and the connection resistance was checked in the same manner as in the evaluation in (9) above, to evaluate impact resistance. The impact resistance was evaluated according to the following criteria, based on the rate of increase in resistance from the average connection resistance obtained in the evaluation in (9) above.

[0206] [Impact resistance evaluation criteria] ○: The increase in resistance from the average connection resistance is 30% or less △: The increase in resistance from the average connection resistance is more than 30% and less than 50% ×: The increase in resistance value from the average connection resistance exceeds 50%.

[0207] (11) Connection reliability after high temperature and high humidity conditions One hundred of the resulting connection structures were left at 85°C and 85% RH for 100 hours. After leaving the connection structures, the 100 connection structures were evaluated for the presence or absence of electrical connection defects between the upper and lower electrodes. The connection reliability after high temperature and high humidity conditions was evaluated according to the following criteria.

[0208] [Criteria for determining connection reliability after high temperature and high humidity conditions] XX: Out of 100 connection structures, the number of those with poor continuity is 1 or less ○: The number of conductive defects is 2 to 5 out of 100 connection structures. △: Of 100 connection structures, the number of structures with poor continuity is 6 to 10. ×: Of 100 connection structures, the number of structures with poor continuity is 11 or more.

[0209] The results are shown in Tables 1 and 2. In Examples 1 to 7 and 9 to 12, electron microscope photographs similar to those in FIG. 8(b) were obtained for the resin particles after compression and release. FIG. 9 shows referenceFig. 10(a) is an electron microscope photograph of resin particles after compression and release in Example 8. Fig. 10(b) is an electron microscope photograph of resin particles after compression and release in Comparative Example 1, Fig. 10(c) is an electron microscope photograph of resin particles after compression and release in Comparative Example 3.

[0210] [Table 1]

[0211] [Table 2] [Explanation of symbols]

[0212] 1...Resin particles 1a…First surface (flat portion) 1b…Second surface (flat part) 2...Conductive part 11...Conductive particles 21...Conductive particles 22...Conductive part 22A…First conductive part 22B...Second conductive part 31...Conductive particles 31a...protrusion 32...Conductive part 32a...Protrusion 33…core substance 34...Insulating material 41...Connection structure 42...First connection target member 42a...first electrode 43...Second connecting member 43a...second electrode 44…Connection 81...Electronic component device 82...first ceramic member 83...Second ceramic member 84...Joint part 84B…Glass 85...Electronic components 86…Lead frame P…Compression direction R…Internal space

Claims

1. Resin particles, The resin particles are thermosetting by heating, the material of the resin particles includes a thermosetting resin; the thermosetting resin is an epoxy resin, The resin particles are spherical in shape, The compressive elastic modulus when the resin particles are compressed by 10% is 100 N / mm 2 More than 3500N / mm 2 is as follows: The resin particles are compressed by 30% relative to their particle diameter, held at 200°C for 10 minutes, and then released from compression, such that the resin particles after release from compression have two planar portions facing each other in the compression direction.

2. 2. The resin particle according to claim 1, wherein a ratio of a major axis of the flat portion of the resin particle after the compression and release to a maximum axis of the resin particle after the compression and release is 0.10 or more and 0.95 or less.

3. The resin particles according to claim 1 or 2, which have a thermal decomposition temperature of 200° C. or more and 350° C. or less.

4. The compressive elastic modulus when the resin particles are compressed by 30% is 100 N / mm 2 More than 3000N / mm 2 The resin particles according to any one of claims 1 to 3, wherein:

5. The resin particles according to any one of claims 1 to 4, which are used for spacers, for adhesives for electronic components, for obtaining conductive particles having conductive portions, or for use as materials for additive manufacturing.

6. The resin particle according to any one of claims 1 to 5, which is used as a spacer for a liquid crystal display element, used as an adhesive for electronic components, or used to obtain conductive particles having a conductive portion.

7. The resin particles according to any one of claims 1 to 6, and a conductive portion disposed on a surface of the resin particle.

8. The conductive particle of claim 7 , further comprising an insulating material disposed on an outer surface of the conductive portion.

9. The conductive particle according to claim 7 or 8, having protrusions on an outer surface of the conductive portion.

10. The conductive particles and the binder resin are included. A conductive material, comprising the resin particle according to any one of claims 1 to 6 and a conductive portion disposed on a surface of the resin particle.

11. A first connection target member; A second connection target member; A connection structure comprising a connection part connecting the first connection target member and the second connection target member, the connection part being formed from the resin particles according to any one of claims 1 to 6 or from a composition containing the resin particles.

12. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion connecting the first connection target member and the second connection target member, the connection portion being formed of conductive particles or a conductive material containing the conductive particles and a binder resin, The conductive particle comprises the resin particle according to any one of claims 1 to 6 and a conductive portion disposed on a surface of the resin particle, A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.

Citation Information

Patent Citations

  • Secondarily deformed anisotropically adhesive spacer particle, manufacturing method therefor and display device using the particle

    JP2003043495A

  • Photosensitive composition, photospacer and method for producing photospacer, protective film, colored pattern, substrate for display device and display device

    JP2009162871A

  • Separating agent and liquid chromatography column

    JP2017037070A

  • Base material particle, conductive particle, conductive material and connection structure

    JP2019046801A

  • Resin particles, conductive particles, conductive material, adhesive, connection structure and liquid crystal display element

    WO2018230470A1